Handbook of Thermoset Plastics - Goodman, Sidney H. (Noyes Publications, 2011)
As a survey of the technology, the handbook provides the reader with the practical implications of crosslinking, as well as establishing relationships between time, temperature, and mass, often ignored in the general overviews allotted to thermoset plastics in other handbooks.